Validation and Discriminant Analysis of the Athens Insomnia Scale in Older Adults - Huseyin Elbi; Melike Batum; Ece Ozlem Oztürk; Merve Vatansever Balcan; Ayşin Kisabay Ak; Hikmet Yilmaz; Omer Aydemir (International Journal of Methods in Psychiatric Research)
ABSTRACT Objective This study aimed to validate and discriminate the “Athens Insomnia Scale” in aged. Methods Patients were assessed using the Athens Insomnia Scale (AIS) and the Pittsburg Sleep Quality Index (PSQI). The internal consistency of the AIS was assessed using the Cronbach alpha coefficient. For validity analyses, the scale's structure validity was evaluated using confirmatory factor analysis (CFA). Besides, known group analyses were performed for demographic features such as age and education variables, and diagnostic groups were analyzed. Results Cronbach's alpha of AIS was found to be 0.881. In the CFA, the goodness of fit indices of the two‐factor model was found to be significant, which supported the two‐dimension structure as a nocturnal sleep problem and its effects on daytime dysfunction. A high correlation was observed between the AIS and the PSQI. It was determined that the discrimination of the > 65 patients from the < 65 patients with AIS was very high, with the discriminating item “frequent nighttime awakenings” in older adults (Wilks' lambda = 0.874). Conclusion The Athens Insomnia Scale is a practical, reliable, and useful tool for evaluating insomnia symptoms in older adults. Its two‐dimensional structure distinguishes nocturnal sleep problems and their effects on daytime functionality.